A new approach to in vitro studies of antigenic response in earthworms - Bilej, M; Tucková, L; Rossmann, P (Developmental and comparative immunology, 1994)
A method for in vitro cultivation of earthworm gut wall tissue explants is described. Tissue explants are able to respond to protein antigen by secretion of antigen-binding protein into the culture medium. Large irregular cells and round-shaped cells are released from tissue explants during the cultivation. This method represents an advantageous tool for in vitro studies providing the possibility of parallel assays from the same donor.
Keywords: Animals; Intestines; střeva; mikroskopie elektronová rastrovací; antigeny helmintové; zvířata; Antigens, Helminth; kultivační média; Microscopy, Electron, Scanning; Culture Media; Oligochaeta